Psychosocial stressors and support needs of survivors of Ebola virus disease, Bombali District, Sierra Leone, 2015 - Waheed Ariyo Bakare; Olayinka Stephen Ilesanmi; Edmund Presiror Nabena; Temitope Famuyide (PAGEPress Publications, 2016)
Ebola virus disease (EVD) survivors are increasing. There is a need to document their psychosocial stressors and support needs to enable appropriate interventions. The aim of this study was to document psychosocial stressors and support needs of EVD survivors in Bombali District, Sierra Leone, in 2015. Qualitative and quantitative methods were used. A cross-sectional study design (questionnaire) was used for quantitative data collection from 299 survivors, while in-depth interview was done for 6 survivors. Parental losses, poor economic situation, joblessness, lack of food were among the problems reported. The median age of survivors was 24 years (range 1- 89 years). Orphans were 66 (22.1%), widows were 59 (19.7%), while widowers were 19 (6.4%). Food was needed by 291 (97.3%) of the survivors, 196 (65.6%) reported they needed clothing. Shelter was the need of 20 (6.7%) survivors, while 246 (82.3%) wanted financial support. In all, 4 (1.4%) survivors were rejected by their families' members, while community members rejected another 4 (1.3%). Ebola survivors are champions and they should be projected in that light within their family and community. Governments need to establish strategic partnership with non-governmental bodies to ensure the needs of the survivors are met.